Anomalous coronary artery originating from the opposite sinus of Valsalva (ACAOS), fractional flow reserve‐ and intravascular ultrasound‐guided management in adult patients. Issue 1 (9th March 2018) - Driesen, Bart W.; Warmerdam, Evangeline G.; Sieswerda, Gert‐Jan T.; Schoof, Paul H.; Meijboom, Folkert J.; Haas, Felix; Stella, Pieter R.; Kraaijeveld, Adriaan O.; Evens, Fabiola C. M.; Doevendans, Pieter A. F. M.; Krings, Gregor J.; van Dijk, Arie P. J.; et al.
Abstract: Objectives: To describe the use of fractional flow reserve (FFR) and intravascular ultrasound (IVUS) in the evaluation of patients with anomalous coronary arteries originating from the opposite sinus of Valsalva (ACAOS). Background: ACAOS of the right and left coronary are rare, but may lead to symptoms and impose a risk for sudden cardiac death, depending on several anatomical features. Assessment and risk estimation is challenging in (nonathlete) adults, especially if they present without symptoms or with atypical complaints. Methods: The team retrospectively studied 30 consecutive patients with ACAOS with interarterial course, who received IVUS‐ and FFR‐guided treatment at our institution between October 2010 and September 2017. Results: FFR was abnormal in only seven patients. IVUS showed the typical slit‐like anatomy of the orifice in 23 patients. Based on FFR and/or IVUS results, in conjunction with the clinical presentation, clinical decision was made. A decision for intervention was made if at least two out of three entities were abnormal. Intervention implied unroofing of the coronary artery ( n  = 10) or coronary artery bypass grafting ( n  = 1). In all other patients a conservative strategy was followed. No adverse events occurred in the total population after a median of 37 (0–62) months of follow‐up. Conclusions: Conservative treatment may be justifiable in adult patients with ACAOS in the presence of normal FFR and nonsuspicious symptoms, despite the presence of an interarterial course and/or slitlike orifice on IVUS. We recommend the use of FFR and IVUS in the standard work‐up for adult patients with ACAOS and propose the use of a flowchart to aid in decision‐making.